Helping at NASA: Guidelines for using process consultation to develop impactful research. Issue 1 (March 2022) - Heracleous, Loizos
Abstract: Management research has long been criticized for its perceived lack of relevance or impact beyond academia. How can we, as management scholars, create research that is more relevant and impactful? I argue that Edgar Schein's process consultation approach can be part of the answer. Process consultation's ultimate aim is to help client organizations. Key aspects of what is now recognized as engaged scholarship were fundamental to process consultation even before engaged scholarship was part of the management vocabulary. Based on my engagement process with the National Aeronautics and Space Administration since 2013, I argue that trust can fruitfully be seen as an outcome and an enabler of productive long-term helping relationships and of engaged scholarship; that what I call pragmatic bricolage is important in terms of offering help based on the client's needs as they develop at different junctures; and that unexpected dilemmas in such relationships are inevitable, but ways forward can be found by applying key principles of social systems. I conclude by outlining guidelines for impactful research and for disseminating research to wider audiences. Highlights: A process consultation approach, by closely engaging the client and their perspective, can help organizations address their challenges and the perceived lack of relevance of management research Trust is both an outcome and an enabler of effective process consultation and engaged scholarship initiatives Pragmatic bricolage is needed in terms of the different roles of the engaged scholar at different junctures of the field experience Dilemmas in the field are inevitable; ways forward can be found based on cornerstone principles of social systems arising from organization change and development, and process consultation Guidelines are offered on how to achieve impactful research through process consultation and how to disseminate research to wider audiences